2022
DOI: 10.3390/agriculture12081233
|View full text |Cite
|
Sign up to set email alerts
|

Design and Experiment of Nondestructive Post-Harvest Device for Tomatoes

Abstract: This paper proposed a whole process tomato harvester with a nondestructive post-harvest collection operation mode, which was aimed to solve the high damage rate problem during the automatic greenhouse tomato harvesting process. The post-harvest device mainly included the net bag mechanism, the conveying and collecting mechanism, whose structure and materials were carefully designed to satisfy the nondestructive collection principle. Numerical simulation was done to evaluate the damage under three working condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Through numerical simulation, Zu et al [36] presented the internal stress distribution of tomatoes, as well as the structural optimization design of a non-destructive post-harvest device, in which the peak contact stress was 107 kPa, close to the maximum pressures recorded by the Grip System. The Grip System apparatus showed that tomato picking by the picker took between 2 and 2.5 s. Similar results regarding harvesting time and picking forces were obtained by Gao et al [5] in their study of a dynamic measurement system for manual picking of cherry tomatoes.…”
Section: Discussionmentioning
confidence: 96%
“…Through numerical simulation, Zu et al [36] presented the internal stress distribution of tomatoes, as well as the structural optimization design of a non-destructive post-harvest device, in which the peak contact stress was 107 kPa, close to the maximum pressures recorded by the Grip System. The Grip System apparatus showed that tomato picking by the picker took between 2 and 2.5 s. Similar results regarding harvesting time and picking forces were obtained by Gao et al [5] in their study of a dynamic measurement system for manual picking of cherry tomatoes.…”
Section: Discussionmentioning
confidence: 96%